Sistem Kontrol Manajemen Pakan Ikan Lele Sangkuriang berdasarkan Usia Benih Ikan dan Jumlah Takaran Pakan - Muhammad Fikri; Mochammad Hannats Hanafi Ichsan; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Errors in catfish feed control can result in food residue in the pond. Leftover food in the pond can cause disease in catfish which results in the death of the fish. To anticipate errors in catfish feed control, a system that is able to regulate catfish feed is needed to prevent food residue in catfish ponds. Fish feed regulation requires differentiating or classifying feed doses based on the age of catfish fry, to minimize wasted food residue. Based on the background that has been described, this research focuses on the design and implementation of a catfish feed control system based on seed age and feed dosage. This research was carried out in a pond with sangkuriang catfish species. This study applies an Arduino microcontroller and an ESP8266 Wif Module which are connected to each other via a serial communication line using an internet connection as the MQTT protocol. Arduino functions as the main control system for the fish feed system to process the input signal from the load cell sensor as a feedback component on the internet of things that can be accessed connected to the system via token input access, then on the blynk interface. the initialization program and configuration of various variations of fish feed doses were applied as input commands aimed at the feed opening and closing actuators until the feed was given to the fish pond. The results of this study indicate that this fish feed control system is able to be a solution to overcome time efficiency and the selection of feed dosage according to the size of sangkuriang catfish.